Impact of Sr2+ doping on the structural, dielectric, ferroelectric and optical properties of YFeO3 perovskite phosphor - Kumar D.; Yadav S.; Singh C.B.; Yadav R.S.; Rai S.B.; Singh A.K. (My University, 2025)
The single phase Y1−xSrxFeO3 perovskite phosphors with x = 0, 0.025 and 0.050 were synthesized by using the sol-gel combustion method followed by calcination at a low temperature. The structural characteristics of Y1−xSrxFeO3 perovskites have been investigated by Rietveld structure refinement using the X-ray diffraction data. The Rietveld refinement shows that the Y1−xSrxFeO3 perovskite crystallizes into an orthorhombic crystal structure with Pnma space group. The average value of crystallite size decreases with increasing concentration of Sr2+ ion at the Y-site; however, the lattice strain increases. The HRSEM images of the phosphors show that the particle size of phosphors decreases with increasing concentration of Sr2+ ion. At room temperature, the dielectric permittivity and the electric polarization of Y1−xSrxFeO3 phosphors increase via the doping of Sr2+ ions. The FTIR spectra confirm the low phonon frequency of Y1−xSrxFeO3 phosphors. The optical band gap of YFeO3 decreased as the doping concentrations of Sr2+ ions increased. The phosphor gives large number of absorption bands at 334, 350, 360, 388, 467 and 482 nm. The Y1−xSrxFeO3 phosphor emits blue, yellow and red emissions on excitations with 350 and 360 nm. The lifetime of excited levels of the phosphor decreases with the contents of Sr2+ ion. The CIE diagram reveals that the emitted color lies in the bluish-magenta visible spectrum region. Therefore, the Y1−xSrxFeO3 phosphors may be applicable in capacitors, display devices and solid-state lighting. © 2023 Elsevier B.V.